Female offspring gestated in hypothyroxinemia and infected with human Metapneumovirus (hMPV) suffer a more severe infection and have a higher number of activated CD8+ T lymphocytes - Funes, Samanta C.; Ríos, Mariana; Fernández-Fierro, Ayleen; Rivera-Pérez, Daniela; Soto, Jorge A.; Valbuena, José R.; Altamirano-Lagos, María J.; Gómez-Santander, Felipe; Jara, Evelyn L.; Zoroquiain, Pablo; Roa, Juan C.; Kalergis, Alexis M.; et al. (Frontiers in Immunology, 2022)
Maternal thyroid hormones (THs) are essential for the appropriate development of the fetus and especially for the brain. Recently, some studies have shown that THs alterations can also alter the immune system development of the progeny and their ability to mount an appropriate response against infectious agents. In this study, we evaluated whether adult mice gestated under hypothyroxinemia (Hpx) showed an altered immune response against infection with human metapneumovirus (hMPV). We observed that female mice gestated under Hpx showed higher clinical scores after seven days of hMPV infection. Besides, males gestated under Hpx have higher lung viral loads at day seven post-infection. Furthermore, the female offspring gestated in Hpx have already reduced the viral load at day seven and accordingly showed an increased proportion of activated (CD71+ and FasL+) CD8+ T cells in the lungs, which correlated with a trend for a higher histopathological clinical score. These results support that T4 deficiency during gestation might condition the offspring differently in males and females, enhancing their ability to respond to hMPV.